Cognition, psychosocial functioning, and health-related quality of life among childhood cancer survivors. Issue 6 (3rd July 2022) - Siegwart, Valerie; Benzing, Valentin; Spitzhuettl, Janine; Schmidt, Mirko; Grotzer, Michael; Steinlin, Maja; Leibundgut, Kurt; Roebers, Claudia; Everts, Regula
ABSTRACT: Long-term sequelae of cancer and its treatment render childhood cancer (CC) survivors vulnerable to cognitive and behavioural difficulties and likely affect their quality of life (QoL). Our aim was to compare levels of cognition, psychosocial functioning, and health-related QoL of CC survivors to healthy controls and examine the associations between these three domains. Seventy-eight CC survivors (age range = 7–16 years, ≥ one year since cancer treatment) and 56 healthy controls were included. Cognition (i.e., fluid intelligence, executive functions, memory, processing speed, and selective attention), psychosocial functioning, and health-related QoL were assessed using standardized tests and questionnaires. The cognitive performance, parent-reported psychosocial behaviour, and health-related QoL of the CC survivors were within the normative range. However, working memory was significantly poorer in survivors than controls, and visuospatial working memory below the normative range was more commonly observed among survivors than among controls. Processing speed significantly predicted survivors' performance in executive functions. Among survivors, greater peer problems were significantly associated with poorer cognitive functions and health-related QoL. Despite the evidence for good intellectual functioning, which might point towards adequate reserves, in some survivors, domain-specific difficulties may emerge years after cancer relating to psychosocial development and QoL.